2021
DOI: 10.1097/mbc.0000000000001068
|View full text |Cite
|
Sign up to set email alerts
|

A mild deficiency of ADAMTS13 is associated with severity in COVID-19: comparison of the coagulation profile in critically and noncritically ill patients

Abstract: Early descriptions of COVID-19 associated coagulopathy identified it as a disseminated intravascular coagulation (DIC). However, recent studies have highlighted the potential role of endothelial cell injury in its pathogenesis, and other possible underlying mechanisms are being explored. This study aimed to analyse the coagulation parameters of critically and noncritically ill patients with COVID-19 bilateral pneumonia, determine if coagulation factors consumption occurs and explore other potential mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The exact dynamic changes of VWF multimeric pattern after COVID-19 still need further study. The majority of studies reported normal or mildly to moderately decreased ADAMTS13:Ac levels [51] , [62] , [70] , [72] , [80] , [87] , and a strongly elevated VWF:Ag/ADAMTS13:Ac ratio in patients with COVID-19 when compared to healthy controls, especially in those with worse illness or in non-survivors [55] , [70] , [80] . We confirmed that lower levels of ADAMTS13:Ac and higher VWF:Ag/ADAMTS13:Ac ratio and VWF:Rco were related to poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1) which is consistent with findings reported by other authors. [ 14 17 ] Of interest, these patients had reduced VWF activity-to-antigen ratio. There are limited studies regarding activity-to-antigen ratios, two of the four which reported significant differences (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 1–3/10.000 Schwangerschaften findet sich eine Immunthrombozytopenie (ITP) mit Thrombozytenzahlen < 50.000/μl [ 12 ]. Die ca.…”
Section: Thrombozytopenieunclassified
“…So kann neben der typischen Thrombose eine COVID-19-Mikroangiopathie (TMA) auftreten. Die Krankheitsbilder ähneln den vorbeschriebenen Erkrankungen einer TTP oder auch eines HUS [ 12 ].…”
Section: Thrombotische Mikroangiopathieunclassified